Decolonizing International Law: between demystifications and resignifications - Cardoso Squeff, Tatiana de A. F. R.; Dassoler Damasceno, Gabriel Pedro (Revista Brasileira de História & Ciências Sociais, 2024)
In the search for the existence of alternatives for how legal relations in International Law are established today, this text starts from the need to demystify International Law as a universal normative set (part I), so that it can thus look into the possibilities of resignifications of its norms from a critical stance, more specifically through the Third World Approaches to International Law – TWAIL (part II), as is already happening in the field of (International Law of) Human Rights since the Decolonial Theory , allowing not only to question the past, but also to obtain social justice for everyone, including the Third World, largely obstructed, hidden and excluded from international normative logic since the advent of modernity. In order to carry out this research of an applied nature, within the scope of international law, the hypothetical-deductive approach method will be used. As far as the objective is concerned, we will carry out an analysis from a descriptive-explanatory-critical point of view. Finally, the method of procedure adopted is mainly bibliographical, selected in a qualitative manner.